Innovation in Medicine and Healthcare 2017 Proceedings of the 5th KES International Conference on Innovation in Medicine and Healthcare (KES-InMed 2017) - Chen, Yen-Wei.; Tanaka, Satoshi; Howlett, Robert J.; Jain, Lakhmi C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This volume focuses on smart medical and healthcare systems (modern intelligent systems for medicine and healthcare) and includes 31 papers presenting recent trends and innovations in medicine and healthcare, including biomedical engineering research and technologies; machine learning and labeling for biomedical visual data analysis and understanding; advanced ICT for medicine and healthcare; and healthcare support systems. Innovation in medicine and healthcare is an interdisciplinary research area, which combines advanced technologies and problem-solving skills with medical and biological science, and smart medical and healthcare systems can provide efficient and accurate solution to problems faced by healthcare and medical practitioners today by using advanced information communication techniques, computational intelligence, mathematics, robotics and other advanced technologies. Discussing the techniques developed in this area, which will have a significant effect on futuremedicine and healthcare, the book is a valuable resource for researchers, students, engineers, and professionals working in the fields of medical systems, medical technology, and intelligent systems.
My Health Info: An Informative mHealth App for Healthcare and Weight Control -- Big Data and Health "Clinical Records" -- Information and Communication Technologies, and the Positive Mental Health in the Seniors -- Prediction and Prevention of Addictions through the Implementation of a Computational Social Simulator -- CFD Simulation of the Oral-Nasal Flow Partitioning during a Breathing Cycle based on the Soft Palate Movement -- Neural Network Backpropagation with Applications into Nutrition -- Automatic and Robust Vessel Segmentation in CT Volumes using Submodular Constrained Graph -- Automatic Segmentation of Cellular/Nuclear Boundaries based on the Shape Index of Image Intensity Surfaces -- A Study of Nuclei Classification Methods in Histopathological Images -- Semi-automatic Segmentation of Paranasal Sinuses from CT Images using Active Contour with Group Similarity Constraints -- The Possibility of Hemorheological Parameters as Precursors of Recurrent Strokes -- Simulation TechnologiesSupporting Collaborative Training for Emergency Medical Services Personnel -- Applications for Mobile Devices and Methodologies for the Disorder Autism -- Training Simulator for Resuscitation of Neonate with High Effectiveness and Low Introduction Cost -- Effects of Depth Cues on the Recognition of the Spatial Position of a 3D Object in Transparent Stereoscopic Visualization -- A Quantitative Study of Local Ternary Patterns for Risk Assessment in Mammography. .
Keywords: Computational intelligence; Biomedical engineering; Computational Intelligence; Biomedical Engineering and Bioengineering